2010
DOI: 10.1080/14786411003754231
|View full text |Cite
|
Sign up to set email alerts
|

HPLC analysis of polyphenols in the fruits ofRubus idaeusL. (Rosaceae)

Abstract: The separation of anthocyanins present in the fruits of 11 varieties of red raspberries (Rubus idaeus L.) was performed by high performance liquid chromatography (HPLC) with a diode-array detector and evaporative light scattering detection (ELSD). The ELSD parameters--drift tube temperature, nebulising gas flow rate and gain value--were optimised to get the best detection and identification of the anthocyanins. The varieties Heritage and Willamette had the simplest anthocyanin sets consisting of only two predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
6
11
0
Order By: Relevance
“…Five anthocyanins, two flavonols, two flavan-3-ols, and one B-type proanthocyanidin were quantified in the raspberry samples (Tables 2 and 3), and the dominant anthocyanin was tentatively identified as cyanidin-3-O-sophoroside confirming finding by others [36,41]. Cyanidin-3-glucosylrutinoside and pelargonidin-3-O-rutinoside were only found in Glen Ample in agreement with Sparzak et al [42], who found differences in polyphenol profile in 11 varieties of red raspberries. Furthermore, the amount of cyanidin-3-O-glucoside in var.…”
Section: Flavonoids In Swedish Berriessupporting
confidence: 87%
“…Five anthocyanins, two flavonols, two flavan-3-ols, and one B-type proanthocyanidin were quantified in the raspberry samples (Tables 2 and 3), and the dominant anthocyanin was tentatively identified as cyanidin-3-O-sophoroside confirming finding by others [36,41]. Cyanidin-3-glucosylrutinoside and pelargonidin-3-O-rutinoside were only found in Glen Ample in agreement with Sparzak et al [42], who found differences in polyphenol profile in 11 varieties of red raspberries. Furthermore, the amount of cyanidin-3-O-glucoside in var.…”
Section: Flavonoids In Swedish Berriessupporting
confidence: 87%
“…Protocatechuic acid, epicatechin and epigallocatechin were obtained from Sigma (Germany). Sanguiin H-6 was isolated according to the previously described procedure [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ellagitannins are a group of hydrolysable tannins distinctive for the family Rosaceae . The main ellagitannin present in Rubus species is sanguiin H-6, which is accompanied by lambertianin C and other ellagitannins in small quantities [ 8 , 9 ]. Ellagitannins, as well as some flavonoids have also been detected in raspberry leaves [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a variety of HPLC detector types have been used including UV, Diode Array, Mass Spec and fluorescence [23-27]. The choice of fluorescence detection is within established analytical parameters for this determination as it offers selectivity and sensitivity for these compounds with the identity of the peaks being established by the use of authentic standards.…”
Section: Resultsmentioning
confidence: 99%